2009
DOI: 10.4103/0028-3886.48805
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural cavernous hemangioma with myelopathy: A rare lesion

Abstract: A case of pure epidural cavernous angioma involving the dorsal region of the spine is presented. The clinical picture was of a slowly progressive compressive myelopathy. Imaging studies only showed a dorsally located epidural mass lesion. Histology confirmed the diagnosis of this rare type of lesion. The patient improved after excision of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…One theory suggested that it originated from dysplasia blood vessel progenitors [19] and one suggested that it may be a vascular malformation developing from telangiectasias that gradually increase in size [6]. The familial and multiple occurrences of these lesions indicate that it was a hereditary disease with genetic and chromosome disorder [21,22]. Infants cavernous indicate it might develop from embryonic omnipotent angioblastic cells or just a congenital vascular dysplasia disease [3,13], however, radiation or trauma-induced hemangioma supported that it was an acquired vascular malformation.…”
Section: Discussionmentioning
confidence: 97%
“…One theory suggested that it originated from dysplasia blood vessel progenitors [19] and one suggested that it may be a vascular malformation developing from telangiectasias that gradually increase in size [6]. The familial and multiple occurrences of these lesions indicate that it was a hereditary disease with genetic and chromosome disorder [21,22]. Infants cavernous indicate it might develop from embryonic omnipotent angioblastic cells or just a congenital vascular dysplasia disease [3,13], however, radiation or trauma-induced hemangioma supported that it was an acquired vascular malformation.…”
Section: Discussionmentioning
confidence: 97%
“…Intradural spinal, extramedullary, cavernous hemangiomas are most frequently found in the adult population (only 4 pediatric cases cited in literature), mostly in women (23), in the thoracic spine -80% of cases (9)(12) or lower thoraco-lumbar region (13) (20), with posterior location within the spinal canal in 93% of cases; also with possible lateral recesses extensions; less common in cervical location (7)(8) and mostly adherent to the nerve root or spinal cord (8) (24). Capillary hemangiomas are found in the skin and soft tissues in younger people, and rarely occur in the central nervous system; more frequent they are located around or attached to nerve roots of cauda equina and conus medullaris (25), extremely rarely intradurally (16) 16,25) Clinical symptomatology at presentation is variable, depending on the size and topography, with the more frequent symptoms beeing: acute spinal pain, radiculopathy and/or myelopathy, progressive gait disturbance, slowly progressive paraparesis, or even asymptomatic -very rare, as in our case (5,18,(26)(27)(28). Cavernous hemangiomas may present in four major clinical patterns: acute episodes of step wise deterioration, slow progression, acute onset with rapid deterioration, and acute onset with gradual decline (10,12,14,15,18).…”
Section: Discussionmentioning
confidence: 97%
“…Capillary hemangiomas are found in the skin and soft tissues in younger people, and rarely occur in the central nervous system; more frequent they are located around or attached to nerve roots of cauda equina and conus medullaris (25), extremely rarely intradurally (16) 16,25) Clinical symptomatology at presentation is variable, depending on the size and topography, with the more frequent symptoms beeing: acute spinal pain, radiculopathy and/or myelopathy, progressive gait disturbance, slowly progressive paraparesis, or even asymptomatic -very rare, as in our case (5,18,(26)(27)(28). Cavernous hemangiomas may present in four major clinical patterns: acute episodes of step wise deterioration, slow progression, acute onset with rapid deterioration, and acute onset with gradual decline (10,12,14,15,18). Acute clinical deterioration is present in cavernous hemangiomas associated with subarachnoid hemorrhage induced by intralesional hemorrhage, lesion growth, thrombotic venous occlusion; bleedind can occur due to the thin-walled vessels, stasis of blood flow in the lesion, estrogen mediated neoangiogenesis in the lesion or drainer compression by a gravid uterus (22)(23) The MRI signal intensity and character of the spinal epidural cavernous hemangioma reflects its histopathology:…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They constitute ∼4% of all epidural tumours and 12% of all intraspinal haemangiomas. Spinal epidural cavernous haemangioma without a primary origin in the vertebral bone is rare, with only 80 cases reported in English literature 5–7 9 10. The patients with this type of lesion usually present in the fifth or sixth decade 11.…”
Section: Discussionmentioning
confidence: 99%